(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Sedentary lifestyles and physical inactivity are becoming increasingly common, which is a major public health concern. Fitness smartwatches have evolved as a popular tool for encouraging physical activity among people of all ages. The purpose of this systematic research has been to look into the effect of fitness smartwatches in promoting active lifestyles among people of various ages. For the purpose of the study structured questionnaire is prepared and collected the responses from 149 respondents. To increase the efficacy of the study , one cross tabulation, one way ANOVA and Descriptive stats tools were used and found that there is a significant difference in smartwatch adoption across different age groups but no significant difference in the perceived benefit and ease of use, even though the majority of respondents use them infrequently and have noticed an increase in their level of physical activity.